"I needed to have this relief": engaging with critical and indigenous methodologies as developing scholars. Issue 10 (26th November 2021) - Masta, Stephanie
Abstract: Developing critical and Indigenous scholars is an important imperative as universities and colleges consider how to address ongoing marginalization within higher education. To do this, we need more curriculum dedicated to supporting scholars undertaking this endeavor. In this introduction, I provide an overview of such a curricular move and highlight articles created by developing scholars who made meaning of their development through a range of research experiences.